Assessing the Efficacy of a Silver Carboxylate Antimicrobial Coating on Prosthetic Liners. Issue 4 (October 2020) - Haglin, Jack M.; Garcia, Dioscaris R.; Roque, Daniel L.; Spake, Carole S.L.; Jarrell, John D.; Born, Christopher T.
ABSTRACT: Introduction: One of the leading issues facing persons with amputation is late development of antibiotic-resistant bacterial infections of the residual limb. To reduce this infection risk, this study assessed the antimicrobial properties and profile of a silver carboxylate complex coating applied to samples of common prosthetic liner materials against pathogens frequently encountered in amputation-site infections. Methods: The antimicrobial efficacy of the coating was measured utilizing a Kirby-Bauer assay with two different types of commercially available prosthetic liners. The assay was run against four pathogens including coagulase-negative Staphylococcus epidermidis, methicillin-sensitive Staphylococcus aureus, Enterococcus faecalis, and multidrug-resistant Acinetobacter baumannii . Observations of bacterial inhibition were made at 24-, 48-, and 72-hr time points for all four pathogens. Dose response curves were created to assess the relative efficacy of the coating against each pathogen independent of prosthetic liners. Graphite furnace atomic absorption spectroscopy (GFAAS) was utilized to measure coating silver elution at 24-, 48-, and 72-hr time points. Results: All conditions of the coating were variably antimicrobial against all tested pathogens in the Kirby-Bauer analysis. Dose response analysis further demonstrated the coating's antimicrobial profile against all tested pathogens. GFAAS demonstrated consistent silver release of the coating throughout 72 hrs. Conclusions: The results of this study suggest the tested antimicrobial coating is effective against a broad range of drug-resistant pathogens. Due to its ability to reduce and inhibit bacterial growth along the prosthetic liner surface, the coating shows promise as an effective tool toward mitigating infection and malodor found at the residual limb-liner interface among persons with amputation.